FAKTOR-FAKTOR YANG MEMPENGARUHI KELELAHAN KERJA PADA PENGEMUDI BUS PRIMAJASA TRAYEK BALARAJA-KAMPUNG RAMBUTAN - Belia, Rizki; Handayani, Putri (Health Publica, 2020)
Driver conditions relating to accidents are driver fatigue. Many factors can lead to fatigue some of them are age, nutritional status, length of employment, workload, time to sleep, and duration of action. Based on operational data obtained from a 10-15 record minor accidents that occurred from early 2018.Loss of concentration in the driver primarily occurs in the morning. State of bustling streets and the lack of concentration of the driver in driving the cause.This study aims to determine the factors that affect the job burnout on the route Balaraja Primajasa bus driver - Kampung Rambutan 2018. This study used cross sectional design with a sample of 35 workers and analyzed using chi square. This study was conducted in February-July 2018. Results of univariate analysis that found that the highest proportion of high fatigue, age is not at risk, risky nutritional status , sleep less, and the duration of the work does not meet standards. The results of the bivariate analysis found that there was no correlation of age with fatigue. There is a relationship  between  nutritional  status,  sleep time  and  duration  of  the  fatigue.The incidence of fatigue in the driver's bus route Balaraja Primajasa - Kampung Rambutan still  high  enough  that  researchers  suggested  for  the  holding  of  the  evaluation  or detection should work fatigue symptoms as early as possible to the driver. Keywords: fatigue, worker, age, risky nutritional status, time of sleep, and duration of work